1997
DOI: 10.1530/eje.0.1360100
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological development in a child with early-treated congenital hypothyroidism as compared with her unaffected identical twin

Abstract: Because the twins were genetically and phenotypically identical, were raised in the same environment, and received a similar education, it is concluded that hypothyroidism in utero and in the first neonatal month was responsible for the lower neuropsychological achievements of the CH twin. While foetal hypothyroidism is at present unavoidable, earlier diagnosis and initiation of treatment in neonates with CH are important and highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
7
1
2
Order By: Relevance
“…Although in our (18,40) and others' (14,15,17,41,42) experience, a low neonatal T 4 level is a risk factor for a defective neuropsychological development, in the present study the degree of neonatal thyroid hormone deficiency was not found to be a major variable influencing school learning. In this regard, our results do not completely agree with the recent observation that a low neonatal T 4 is associated with less satisfactory scores for educational attainments (21).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Although in our (18,40) and others' (14,15,17,41,42) experience, a low neonatal T 4 level is a risk factor for a defective neuropsychological development, in the present study the degree of neonatal thyroid hormone deficiency was not found to be a major variable influencing school learning. In this regard, our results do not completely agree with the recent observation that a low neonatal T 4 is associated with less satisfactory scores for educational attainments (21).…”
Section: Discussioncontrasting
confidence: 64%
“…In some follow-up programmes for CH, global IQs of children treated early in life do not differ from those of control children (1, 3). Other follow-up studies report a mild decrease in global IQs compared with controls (10)(11)(12)(13)(14)(15)(16)(17)(18). Differences in motor and psychometric subtests have also been reported.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results showed from the three Speechlanguage Pathology fields investigated, language was the one with higher number of published papers [16][17][18][19][20][21][22][23][24][25][26] . This allows the arguing about this topic in CH children to be more clear and consistent, but do not exclude the importance of other communication aspects.…”
Section: Methodsmentioning
confidence: 99%
“…Subtitles: SG= study group; CG = control group Figure 2 -Contents of localized papers about speech-language disturbances related to congenital hypothyroidism significant delay in language development [17][18][19][20][22][23][24]26 .…”
Section: Michelsson Et Al;1976 25mentioning
confidence: 99%